A multimodal discourse analysis of glocalization and cultural identity in three Indian TV commercials. (June 2016) - Dash, Amarendra Kumar; Patnaik, Priyadarshi; Suar, Damodar
Improvising selected tools from Kress and Van Leeuwen's inter-semiosis framework, this study explores how, between global and local, TV commercials in India often reframe a cultural third space producing new discursive forms and identities. Three commercials from the food and beverage category are selected on the basis of the country of origin of the endorsing company and the patterns of glocalization. Multimodal discourse analysis reveals that the commercials construct the glocal identity in several ways. In the Knorr Soups commercial, the melody of the title song is contemporary pop, whereas the delivery style and crooning are distinctively Western. The language is predominantly Hindi with deft use of selected English words. The Funda Mint commercial casts a rebel voice-support executive who rejects the pseudo-glocal identity and asserts his true identity. In the Cadbury Bournvita Folk commercial, the two boys represent the global and the local in the realm of creativity. The study advances the knowledge of product positioning and brand identity involving the intersemiosis of discursive elements from different cultural spaces within the contemporary Indian consumerist culture.